List Of Committee - List Of Committee (PROCEEDING UMSURABAYA, 2019)
Steering committee            : Endah Hendarwati, S.E., M.Pd. ( Dean of FKIP)                                              Drs. Yarno, M.Pd. (Vice Dean I of FKIP)                                               Ratno Abidin, S.Pd., M.Pd. ( Vice Dean II of FKIP) Organizing committeeChairperson                            : Drs. H. Wijayadi, M.PdSecretary                                : Vega Hesmatantya, S.Pd.,M.Pd.Treasurer                                 : Ari Setyorini, S.S., MA.Divisions                       1. Conference                            : Sulton Dedi Wijaya, S.Pd., M.Pd.                                                   Sofi Yunianti, S.S.,M.Pd.                                                   Jepri Ali Saiful, S.Pd., M.Ed 2. Workshop                             : Linda Mayasari, S.Pd. M.Pd.                                                   Armeria Wijaya, S.S., M.Pd3. Alumni Gathering                   : Sri Lestari, S.Pd.,M.Hum                                                   Ro’ifah, S.Pd., M.Pd.4. Proceeding                                       : Dr. Dwijani Ratnadewi, M.Pd5. Food and Beverages                          : Waode Hamsia, S.Pd., M.Pd.6. Publication and Design                       : Radius Setiawan, S.Pd., M.A.7. Documentation and Properties            : Pramudana Ihsan, S.Hum., M.Pd.